Are Probiotics or Prebiotics Useful in Pediatric Irritable Bowel Syndrome or Inflammatory Bowel Disease? - Guandalini, Stefano (Frontiers in Medicine, 2014)
Treatment options for irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) are notoriously either inadequate (IBS) or loaded with potentially serious side effects and risks (IBD). In recent years a growing interest for effective and safer alternatives has focused on the potential role of probiotics and their metabolic substrates, prebiotics. It is in fact conceivable that the microbiome might be targeted by providing the metabolic fuel needed for the growth and expansion of beneficial microorganisms (prebiotics) or by administering to the host such microorganisms (probiotics). This review presents a concise update on currently available data, with a special emphasis on children. Data for prebiotics in IBS are scarce. Low doses have shown a beneficial effect, while high doses are counterproductive. On the contrary, several controlled trials of probiotics have yielded encouraging results. A meta-analysis including 9 randomized clinical trials in children showed an improvement in abdominal pain for Lactobacillus GG, Lactobacillus reuteri DSM 17938 and the probiotic mixture VSL#3. The patients most benefitting from probiotics were those with predominant diarrhea or with a post-infectious IBS. In IBD, the use of prebiotics has been tested only rarely and in small scale clinical trials, with mixed results. As for probiotics, data in humans from about 3 dozens clinical trials offer mixed outcomes. So far none of the tested probiotics has proven successful in Crohn’s disease, while in ulcerative colitis a recent meta-analysis on 12 clinical trials (1 of them in children) showed efficacy for the probiotic mixture VSL#3 in contributing to induce and to maintain remission. It is evident that this is a rapidly evolving and promising field; more data are very likely to yield a better understanding on what strains and in what doses should be used in different specific clinical settings.